Therapeutic Application of Cupping Therapy (Hijama): A Brief Review: Application of Cupping Therapy - Niazi, Madiha Khan; Hassan, Farooq; Zaidi, Syed Zahoor Ul Hassan; Ghaffar, Saira; Sohail, Zuha; Noor, Talha; Aamir, Zeerak; Ismail, Muhammad Amjad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Hijama is a form of Unani medicine that involves using heat or suction to partially vacuum a Hijama glass placed on the surface of the body in order to remove disease-causing material or divert it from the diseased area, return displaced organs to their proper positions, and encourage blood flow to the intrusion site. The cups used to administer hijama therapy gave the treatment its name. For sucking purposes, glass or wooden cupping glasses are employed, and a vacuum pump creates the suction. Hijama involves placing a cup to a specific area of the body and sucking blood from there. Hijama is a method of Istifragh that removes the disease's root cause.